The Integration of the Dasabidharāja Dhamma Principles to Promote the Governance of the Songkhla Provincial Administrative Organization - loeslap, chakkrit; Nuthongkaew, Kantaphon (Journal of MCU Phetchaburi Review, 2026)
1. A general overview of the application of the Ten Royal Virtues in promoting the governance of the Songkhla Provincial Administrative Organization reveals that public expectations regarding good governance include honesty, transparency, accountability, and the reduction of corruption, favoritism, and patronage. These are crucial conditions for building trust in a people-centered approach that considers the common good without discrimination. This also encompasses the development of infrastructure and public services, improved quality of life, economic development, tourism promotion, agriculture, border trade, sports, and community product promotion, thereby increasing income distribution. 2. Adopting the Ten Royal Virtues as an ethical framework for the governance of the Songkhla Provincial Administrative Organization helps guide the exercise of power by leaders and administrators to be based on honesty, selflessness, fairness, and prioritizing the public interest over personal gain. This ensures transparent, fair, and accountable administration. Integrating the Ten Royal Virtues promotes policies, structures, oversight mechanisms, and organizational culture to build political legitimacy, enhance trust, and lead to transparent, participatory, and sustainable local governance. 3. New knowledge gained from research on integrating the Ten Royal Virtues to promote the governance of the Songkhla Provincial Administrative Organization is the "SONGKHLA Model." This is a management framework that combines the Ten Royal Virtues with modern good governance principles to create legitimate, transparent, and sustainable governance, with eight key components. The aspects include: 1) Sustainable, 2) Open Wide open 3) Noble (high moral character), 4) Governance good governance, 5) Knowledge , 6) Harmony ( harmony) , 7) Loyalty ; 8) Area/ Space and Environment Keywords: Integration, Ten Royal Virtues, Promotion, Provincial Administrative Organization